Shrimp zircon geochronology constrains on Permian pyroclastic levels, Claromecó Basin, South West margin of Gondwana, Argentina. (August 2018) - Arzadún, Guadalupe; Tomezzoli, Renata N.; Trindade, Ricardo; Gallo, Leandro C.; Cesaretti, Nora N.; Calvagno, Juan M.
Abstract: Pyroclastic levels are descripted in Sierras Australes outcrops and Claromeco Basin sub-surface records, interbedded with mudrocks and coal beds in the base of the Tunas Formation sequence that correspond to the Permian South West margin of Gondwana. The pyroclastic levels classify as fine tuff. SHRIMP zircon ages obtained are 291.7 ± 2.9 Ma in the outcrop and 295.5 ± 8.0 Ma in the subsurface. These ages are consistent with other zircon SHRIMP ages of other outcrops tuff of the Tunas Formation, with Permian flora, and with tuff ages of correlated Gondwana areas, in the Paraná, Karoo and Paganzo basins. These data, in addition with other geological evidences, support a tectonically active and changing environment during the Permian of Gondwana. The ages allowed calculating a northward latitudinal speed of 2.7 cm/year for Gondwana during the Permian. This latitudinal movement is explained as the consequence of the final coupling of several continental microplates, gradually amalgamated from the southern margins of Gondwana and from the northern of Laurentia to configure the final Pangea during the Triassic. Since the main accretions in the southwestern margin of Gondwana could have started during the Devonian - Carboniferous, this Permian orogeny (San Rafael Orogenic Phase in Argentina) would be representing the post - collisional deformation, with a peak of compression in the Early Permian that was attenuating towards the foreland during the Late Permian - Early Triassic. With these results, it is also possible to constraint the age of the upper Paleozoic glaciation up to 295, previous to the deposition of the Tunas Formation in the Sauce Grande Formation. Graphical abstract: Image 1 Highlights: The radimetric ages obtained in the Tunas Formation tuffs are 291.7 and 295.5 Ma and indicate a tectonically active environment. It is also possible to constraint the age of the upper Paleozoic glaciation. The latitudinal movement speed of Gondwana was 2.7 cm/year during the Permian and would be the consequence of the final coupling of several continental microplates.